Akibat Hukum Notaris Tidak Memasukkan Salah Satu Ahli Waris Dalam Akta Keterangan Waris - Rochmawati Rochmawati; Moh. Saleh (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The legal consequences of notaries not including one of the heirs in the deed of inheritance is a problem that often occurs in notary practice in Indonesia. The purpose of this research is to analyze the legal consequences of the actions of a notary who does not include one of the heirs in the deed of inheritance. The research method used is normative juridical with a statutory regulation approach, namely through library research and analysis of legal documents. The results of the study show that the actions of a notary who does not include one of the heirs in the deed of inheritance can result in the invalidity of the deed through a lawsuit for canceling the deed. Therefore, the notary must comply with the applicable laws and regulations and carefully examine the identities of all heirs involved in making the deed of inheritance.